Multidisciplinary and Interdisciplinary Perspective on Hand Burns: Physiotherapy, Occupational Therapy - ÖZALP, Muhammed; ERDOĞAN, Emre (MAS Journal of Applied Sciences, 2024)
Burns can occur for many reasons. While burns vary according to their degree, they can cause physical, sensory and social problems in human life. Among the main problems, deformities occur in individuals with burn problems, making it difficult to participate in sensory sensitivity, motor skills and daily life activities. Due to these problems that occur in individuals, they cause serious problems in daily life and business life. It is aimed to increase the living standards of individuals with hand burns and upper extremity burns from a multidisciplinary and interdisciplinary perspective and to carry out rehabilitation interventions in a health way. A comprehensive rehabilitation program should be implemented to prevent complications that may occur during the physiotherapy rehabilitation process and to return the individual to his or her previous functional level. Physiotherapy helps maintain functionality and integrate into society with edema method, exercise, positioning and orthosis methods. The main goal of the occupational therapy rehabilitation process is to increase independence and improve the quality of life. While occupational therapists intervene in upper extremity burns, they provide auxiliary materials such as compression garments and splints for positioning, pressure and scar control, as well as supporting the individual’s social participation and evaluating occupational participation.